Properties of Mortar With Addition of Fiber From Polymeric Waste - Omonov Musobek; Raxmatov Ilxom; Mannatov Botir, (European Journal of Life Safety and Stability (2660-9630), 2022)
In this paper the authors present the possibility to utilize some asphalt building waste materials to produce simple concrete. To prepare the mixes, Recycled Concrete Aggregate as a small aggregate of 0.16-5 mm fraction were used. Concretes with waste were mixed with 300 kg/m2 of four types of cements. The concrete sample specimens were tested for mechanical properties which are related to durability. After 28 days compressive strength increase to 45 MPa and after 90 days 50 MPa were achieved. Polymer-modified mortar and concrete are prepared by mixing either a polymer or monomer in a dispersed, powdery or liquid form with fresh cement mortar and concrete mixtures, and subsequently cured, and if necessary, the monomer contained in the mortar or concrete is polymerized in-situ.